On the Concept of "Developing Countries" - Tauber, Arnošt (Czech Journal of International Relations, 1966)
In this discussion contribution, the point is not to deal with the terminological question, comment on whether the so-called the developing world should be labeled as "developing countries" or "economically less developed country", "economically underdeveloped countries","land of undeveloped capitalism", or call them by other possible names, or to keep the name "countries of Asia, Africa and Latin America", but to try to establish some basic criteria characteristic of the area of ​​the world that we freely label, maybe not too happy, for development. Developing countries usually include politically sovereign African states with South Africa, Asia with the exception of Japan and Israel, and Latin America with the exception of Cuba. If we use the term developing countries, then they belong to this group even territories in these areas that have not yet achieved state sovereignty and still have colonies.